PENGUATAN KESADARAN MITIGASI PEMANASAN GLOBAL MELALUI PROYEK PEMANFAATAN SAMPAH PLASTIK BERBASIS PEMBELAJARAN INTERDISIPLINER DI SEKOLAH - Ni Wayan Sukmawulandari; Ulfiani Ulfiani; Melani Putri; Santi Sanda; Epin Purnama; Abd.Rahim Yusuf; Jahring Jahring (COMMUNITY : Jurnal Pengabdian Kepada Masyarakat, 2026)
Global warming and the increase in plastic waste have become increasingly urgent environmental issues, while learning practices in schools still tend to be informative and fragmented, making them less capable of building a comprehensive awareness of mitigation among students. This community service research focuses on strengthening awareness of global warming mitigation through an interdisciplinary learning-based plastic waste utilization project in secondary schools. The method used is a descriptive quantitative approach with a one group pretest-posttest design involving 21 students, carried out in 3 stages. The stages of the activity included (1) planning activities in the form of observation, (2) implementation activities in the form of delivering brief material on global warming and the contribution of plastic waste to greenhouse gas emissions, implementing a plastic waste utilization project in groups integrated with physics lessons, and (3) evaluation activities in the  form  of  administering  pre-tests  and  post-tests.  The  research  instrument  was  a questionnaire on global warming mitigation awareness, while the data were analyzed descriptively using mean values and standard deviations. The results showed that the average awareness score of the students increased significantly from 23% on the pre-test to 96% on the post-test, with all participants experiencing an increase in their scores. These findings indicate that project-based interdisciplinary learning on plastic waste utilization is effective in raising students' awareness of global warming mitigation through contextual and participatory learning experiences. The main conclusion of this study confirms that the integration of real plastic waste management projects in schools has the potential to become a relevant learning strategy for building students' environmental awareness and responsibility.